1997
DOI: 10.1037/0033-2909.122.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Trials and tribulations in the meta-analysis of treatment differences: Comment on Wampold et al. (1997).

Abstract: A fair test of the Dodo bird conjecture that different psychotherapies are equally effective would entail separate comparisons of every pair of therapies. A meta-analysis of overall effect size for any particular set of such pairs is only relevant to the Dodo bird conjecture when the mean absolute value of differences is 0. The limitations of the underlying randomized clinical trials and the problem of uncontrolled causal variables make clinically useful treatment differences unlikely to be revealed by such he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 27 publications
0
49
0
1
Order By: Relevance
“…This frequently observed "dodo bird verdict" (e.g., Luborsky, 1975;Luborsky et al, 1995;Wampold, Mondin, Moody, Stich, et al, 1997; but see objections by Crits-Cristoph, 1997, andHoward et al, 1997, and a rejoinder by Wampold, Mondin, Moody, and Ahn, 1997), so named because of the dodo bird's statement in Alice in Wonderland that all have won and all must have prizes, is suggested by extensive meta-analyses that indicate few differences between alternative forms of treatment (e.g., Frank, 1979;Smith, Glass, and Miller, 1980;American Psychiatric Association Commission on Psychotherapies, 1982;Shapiro and Shapiro, 1982). These similarities suggest that either common processes are shared by various therapeutic approaches (Frank, 1982;Strupp and Binder, 1984), such that they are functionally equivalent (Lambert, Shapiro, and Bergin, 1986;Stiles, Shapiro, and Elliot, 1986), or that research has not adequately addressed major methodological issues (e.g., VandenBos and Pino, 1980;Wortman, 1983;Kazdin, 1986).…”
Section: Critique Of Symptom-focused Researchmentioning
confidence: 93%
“…This frequently observed "dodo bird verdict" (e.g., Luborsky, 1975;Luborsky et al, 1995;Wampold, Mondin, Moody, Stich, et al, 1997; but see objections by Crits-Cristoph, 1997, andHoward et al, 1997, and a rejoinder by Wampold, Mondin, Moody, and Ahn, 1997), so named because of the dodo bird's statement in Alice in Wonderland that all have won and all must have prizes, is suggested by extensive meta-analyses that indicate few differences between alternative forms of treatment (e.g., Frank, 1979;Smith, Glass, and Miller, 1980;American Psychiatric Association Commission on Psychotherapies, 1982;Shapiro and Shapiro, 1982). These similarities suggest that either common processes are shared by various therapeutic approaches (Frank, 1982;Strupp and Binder, 1984), such that they are functionally equivalent (Lambert, Shapiro, and Bergin, 1986;Stiles, Shapiro, and Elliot, 1986), or that research has not adequately addressed major methodological issues (e.g., VandenBos and Pino, 1980;Wortman, 1983;Kazdin, 1986).…”
Section: Critique Of Symptom-focused Researchmentioning
confidence: 93%
“…Despite this record going back almost 25 years to the meta-analysis of therapy outcomes performed by Smith and Glass (1977), Luborsky et al (this issue), Crits-Christoph (1997), and others continue to hold out the possibility or even the likelihood of finding significant differences among the therapies. In a similar vein, Howard, Krause, Saunders, and Kopta (1997) suggested that therapies should be ordered along an efficacy continuum. Luborsky et al's meta-meta-analysis places us no closer to either goal than have the previous meta-analyses, precisely because the evidence points to all active therapies being equally beneficial.…”
Section: Interaction Effectsmentioning
confidence: 99%
“…effect of any therapy, only, at best, its difference from the others in terms of patient outcome. One therapy may be much better than another and good enough in one randomized experiment without being good enough at the other levels of the unmanipulated variables that we would encounter in another such experiment (Howard, Krause, Saunders, & Kopta, 1997). Thus, we cannot conclude from a statistically proper interpretation of the results of randomized clinical trials if any of the therapies compared should be assigned to any specific patient even though we have evidence for which is the best on average at the unique (but undefined) location or, more likely, set of locations in C at which the trials occurred.…”
Section: Nature Purpose and Methods Of Between-group Therapy Outcommentioning
confidence: 95%